RHETORICAL TRANSFER LOCALIZATION: THE JOURNEY OF MAJAZ FROM ARABIC TI PERSIAN (11th-14th CENTURIES) - Mohammad Osman Mehedi (Muaddib: Journal of Arabic Language and Literature, 2026)
The transfer of Arabic rhetorical concepts into Persian literary theory represents a significant process of intellectual and literary exchange in the medieval Islamicate world. This study examines how majāz and related rhetorical figures, including tashbīh, istiʿārah, kināyah, and laff wa al-nashr, were transmitted, reinterpreted, and creatively localized in Persian rhetoric from the fifth to the eighth centuries AH (eleventh–fourteenth centuries CE). Employing a historical-comparative and textual-analytical method, the study compares selected passages from three major Arabic rhetorical works—al-Jāḥiẓ’s Al-Bayān wa al-Tabyīn, Ibn al-Muʿtazz’s Al-Badīʿ, and al-Jurjānī’s Asrār al-Balāghah—with three foundational Persian works: Rādūyānī’s Tarjumān al-Balāghah, Waṭwāṭ’s Ḥadāʾiq al-Siḥr, and Shams Qays al-Rāzī’s al-Muʿjam. The findings reveal that Persian rhetoricians did not merely borrow Arabic rhetorical categories but selectively appropriated and reformulated them according to Persian linguistic structures and poetic conventions. The treatment of laff wa al-nashr particularly illustrates this creative localization through more complex patterns of arrangement and inverted correspondence. The study concludes that rhetorical transfer functioned as a process of transformation rather than simple transmission, demonstrating that cross-linguistic exchange generated new forms of rhetorical knowledge within Persian literary theory.